Studies on the concerted interaction of microbes in the gastrointestinal tract of ruminants on lignocellulose and its degradation mechanism - Runqi Fu; Runqi Fu; Lin Han; Lin Han; Qian Li; Qian Li; Zhe Li; Yue Dai; Jing Leng; Jing Leng (Frontiers in Microbiology)
The complex structure of lignocellulose, one of the most abundant renewable resources on earth, makes biodegradation challenging. Ruminant gastrointestinal microbiota achieves efficient lignocellulose degradation through a highly synergistic ecosystem, which provides an important research model for sustainable energy development and high value-added chemical production. This review systematically summarizes the key mechanisms of lignocellulose degradation by ruminant gastrointestinal microorganisms, focusing on the synergistic roles of rumen and hindgut (including cecum, colon, and rectum) microorganisms in cellulose, hemicellulose, and lignin degradation. The study focuses on the functional differentiation and cooperation patterns of bacteria, fungi and protozoa in lignocellulose decomposition, and summarizes the roles of carbohydrate-active enzymes (CAZymes) and their new discoveries under the histological techniques. In addition, this manuscript explores the potential application of gastrointestinal tract (GIT) microbial degradation mechanisms in improving the utilization of straw-based feeds. In the future, by revealing the mechanism of microbe-host synergy and integrating multi-omics technologies, the study of ruminant gastrointestinal microbial ecosystems will provide new solutions to promote the efficient utilization of lignocellulose and alleviate the global energy crisis.